Management of marginality with approach to the empowerment in Mashhad - Hosseinzadeh, Sara; Alizadeh, Katayoon; Jafari, Hamid (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
In this paper, the reasons for marginal growth in Mashhad were examined. Marginalization in the areas around the city was reviewed and the margin management in the direction of empowerment was evaluated. The main goal is to find solutions for better management of marginalized areas based on empowerment approach. Research method is descriptive-analytic and data are obtained through documentary and field studies (completed questionnaires). In order to test the research hypotheses, statistical analysis of factor analysis, analysis of variance, Spearman correlation coefficient and Mann-Whitney test have been used. The statistical population consists of 922282 people in eight marginal areas of Mashhad that includes 66 marginal neighborhoods. From statistical population, 400 people were selected as samples. To obtain sample size, the Cochran formula has been used with a 95% confidence interval and a standard error of 5%. The research findings show that the best solution for better management of the marginalized areas is the economic empowerment of the marginalized population, which, of course, has been implemented for empowerment. In the field and practical part, 384 randomly selected questionnaires were completed by residents of marginal neighborhoods of Mashhad. Finally, in the analytical section, the information obtained in the above steps was analyzed using the SPSS software program.